2020
DOI: 10.1371/journal.pone.0240679
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of highly-cited green patents: The perspective of network characteristics

Abstract: With the rise of green technology, green patent value evaluation has become critical for enterprises. In order to explore the influencing factors of green patent value, this study takes the light-emitting diode (LED) industry as an example and then utilizes highly-cited green patents as the proxy of green patent value. The study aims to explore the influencing factors of green patent value with network position and structure from the perspective of network characteristics. The results indicate that out-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Additionally, there are also scholars conducting an in-depth analysis of the practical significance of patent citation networks based on the characteristics of topological networks. Some of them focus on studying the network characteristics [21] of patent citation networks such as small-world and scale-free. Some scholars have studied the technology trajectory of a specific industry in combination with the characteristics of the patent citation network [22].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are also scholars conducting an in-depth analysis of the practical significance of patent citation networks based on the characteristics of topological networks. Some of them focus on studying the network characteristics [21] of patent citation networks such as small-world and scale-free. Some scholars have studied the technology trajectory of a specific industry in combination with the characteristics of the patent citation network [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At this stage, most scholars have seen the impact of patent-related attribute characteristics on patent citation [24]. With the deepening of the research on patent citation relationship especially by social network analysis method, some scholars have found that some local or overall structural features of the patent citation network itself or others will have an impact on the citation relationship [21]. At the same time with the research on the influencing factors of patent citation, there is also a heated discussion on the research methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One representative example is patent data produced by the USPTO, and particularly, the current organization of patent data in terms of IPC sections which provides the tools to address central questions of network analysis such as those derived in the study of different technological domains [ 21 ]. Many studies investigate technological and innovation activities by referring to links between nodes and the resulting networks [e.g., 17 , 41 43 ]. However, the metrics identified (at both node and network level) are mostly discussed from an economic perspective in only one field of technology or one geographic region.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The general process of the econometric model method is: firstly, several factors related to patent value are selected, and then the coefficients of each factor are determined by qualitative or quantitative methods, and finally the econometric model is formed. Rong Chao [7] and Chai [8] used Logistic regression model to regression the factors related to patent value and determine the coefficients of each factor. Fischer et al [9] applied cox regression method to patent valuation; Lee et al [10] established a negative binomial regression model for analysis.…”
Section: Introductionmentioning
confidence: 99%